KECENDERUNGAN KORBAN PELECEHAN SEKSUAL DI TEMPAT KERJA DITINJAU DARI TIPE KEPRIBADIAN PADA WANITA MINANG: TYPES OF PERSONALITY AND TENDENCY TO BE VICTIMS OF SEXUAL HARASSMENT IN THE WORKPLACE - Rida Yanna Primanita; Suci Rahma Nio; Vira Yuliani (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2021)
Introduction Types of personality and tendency to be victims of sexual harassment in the workplace. The purpose of this research is to see the tendency of the victims of sexual harassment towards women workers in terms of personality types in West Sumatra. Method This research is a comparative quantitative type and analyzes using statistical techniques of non-parametric difference test. The population of this research is Minang ethnic women who work in West Sumatra and experience sexual harassment at work, using snowball sampling techniques. The research instrument uses the sexual harassment scale and Myers Brigss Type Inventory. Results Based on the results, the value of Sig = 0.052 (Sig <0.05), it means that there is no significant difference in the level of sexual harassment experienced by Minang ethnic women in the workplace in terms of their personality types. The result also shows that the majority of ethnic Minang women in this research experienced sexual harassment in the workplace in the medium category. Conclusion and Recommendation Based on the results of research and hypothesis, it can be concluded The level of sexual harassment in the workplace experienced by Minang ethnic women is in the medium category, and There is no level of sexual harassment in the workplace experienced by Minang ethnic women based on their personalities. Minang ethnic women are suggested to be more careful in establishing relationships at work, as well as increase their knowledge about forms of sexual harassment and ways to minimize it. The workplace owners are expected to have clear and firm regulations on sexual harassment behavior in the working area. The next reseach is suggested to continue research related to the theme of sexual harassment in Minang ethnic women by using other variables which are assumed to be related to sexual harassment behavior. ABSTRAK Pendahuluan Tipe kepribadian dan kecenderungan menjadi korban pelecehan seksual di tempat kerja pada wanita etnis Minang. Penelitian ini bertujuan untuk melihat kecendrungan menjadi korban pelecehan seksual pada wanita bekerja ditinjau dari tipe kepribadian di Sumatera Barat. Metode Penelitian ini berjenis kuantitatif komparatif dan dianalisa menggunakan teknik statistika uji beda non-parametric. Populasi penelitian ini adalah wanita etnis Minang yang bekerja di Sumatera Barat yang mengalami pelecehan seksual di tempat kerja, dengan teknik pengambilan sampel snowball. Instrumen penelitian yang digunakan skala sexual harassement dan Myers Brigss Type Inventory. Hasil Berdasarkan hasil perhitungan diperoleh nilai Sig =0,052 (Sig<0,05), artinya tidak terdapat perbedaan yang signifikan pada tingkat pelecehan seksual yang dialami wanita etnis Minang di tempat kerja ditinjau dari tipe kepribadiannya. Kesimpulan dan Saran Berdasarkan hasil penelitian dapat disimpulkan bahwa tingkat pelecehan seksual di tempat kerja yang dialami wanita etnis Minang berada pada kategori sedang, dan tidak terdapat tingkat pelecehan seksual di tempat kerja yang dialami wanita etnis Minang berdasarkan tipologi kepribadian yang dimiliki. Bagi wanita etnis Minang disarankan untuk dapat lebih meningkatkan kehati-hatiannya dalam menjalin relasi di tempat kerja, serta meningkatkan wawasan mengenai bentuk-bentuk pelecehan seksual dan cara untuk meminimalisir hal itu terjadi pada diri sendiri. Kata kunci : Pelecehan seksual, wanita bekerja, etnis Minang, tipe kepribadian Myers Briggs